Redescription of the damsel-dragonfly Parafleckium senjituense on the basis of a more complete specimen (Odonata: Isophlebioptera: Campterophlebiidae) - Li, Yongjun; Nel, André; Ren, Dong; Pang, Hong (Zootaxa, 2012)
Parafleckium senjituense Li et al., 2012 is of great importance to clarify the phylogeny of the superfamily Isophlebioidea, as it has several significant structures considered as typical of either Campterophlebiidae or Isophlebiidae (Li et al. 2012). But the established genus and species was based on forewings only. We describe a new specimen, allowing precise description of some other important characters, especially those of the male hindwing. On the basis of this specimen, the diagnosis of Parafleckium senjituense is amended.